Remaining Service Life Discharge Conveyor F pada Tambang Batubara PT XYZ di Kabupaten Sarolangun Provinsi Jambi - La Ode Arlin; Elfida Moralista; Noor Fauzi Isniarno (Bandung Conference Series: Mining Engineering, 2023)
Abstract. A conveyor is a type of conveyance used to transport mineral materials such as coal. The conveyor's structure is made of carbon steel. However, the conveyor's quality may suffer from corrosion caused by direct contact with coal impurities and their environment. The average air temperature was 27.830C, the average rainfall was 235.34 mm, and the relative humidity was 88.48%. The purpose of this study is to determine the type of corrosion, corrosion control conditions, specifically the coating used, corrosion rate, and the conveyor's remaining service life. Methodology in this research is measuring the thickness reduction of conveyor structure to determine corrosion rate and remaining service life. This research was conducted on a conveyor structure consisting of 4 segments with 32 test points along 142 meters. The actual thickness measurement of the conveyor structure is carried out using Ultrasonic Thickness Gauge TT 130. Type of corrosion that occurs in the conveyor structure is uniform corrosion. Corrosion control method applied to the conveyor structure is coating method. Coating used is a primer coating using Seaguard 5000, intermediate coating using Sherglass FF and top coating using Aliphatic Acrylic Modified Polyurethane. Corrosion rate on conveyor structure is 0.1857 – 0.3357 mm/year and is included in good category based on the relative corrosion resistance of steel. Remaining service life of conveyor structure is 6.580 – 9.138 years and based on the design life, which is 15 years, there are 12 test points or 37.5% test points which are predicted to not reach the design life of conveyor structure. Abstrak. Conveyor merupakan salah satu alat angkut yang digunakan untuk memindahkan material bahan galian seperti batubara. Struktur conveyor yang digunakan berbahan dasar baja karbon. Namun demikian struktur conveyor dapat mengalami penurunan kualitas yang diakibatkan oleh korosi yang terjadi karena kontak langsung dengan pengotor batubara dan lingkungannya. pengamatan kondisi lingkungan meliputi temperatur udara rata-rata 27,830C, curah hujan rata-rata 235,34 mm dan kelembapan relatif 88,48%. Penelitian ini bertujuan untuk mengetahui jenis korosi, kondisi pengendalian korosi yaitu coating yang diaplikasikan, laju korosi, dan sisa umur pakai struktur conveyor. Metodologi dalam penelitian ini adalah pengukuran pengurangan ketebalan struktur conveyor untuk mengetahui laju korosi dan sisa umur pakai. Penelitian ini dilakukan pada struktur conveyor yang terdiri dari 4 segmen dengan 32 test point sepanjang 142 meter. Pengukuran tebal aktual struktur conveyor dilakukan dengan menggunakan alat Ultrasonic Thickness Gauge TT 130. Jenis korosi yang terjadi pada struktur conveyor yaitu korosi merata. Metode pengendalian korosi yang diaplikasikan pada struktur conveyor yaitu metode coating three layer. Coating yang digunakan adalah primer coating menggunakan Seaguard 5000, intermediate coating menggunakan Sherglass FF dan top coating menggunakan Aliphatic Acrylic Modified Polyurethane. Laju korosi pada struktur conveyor yaitu 0,1857 – 0,3357 mm/tahun dan termasuk ke dalam kategori good berdasarkan ketahanan korosi relatif baja. Sisa umur pakai struktur conveyor yaitu 6,580 – 9,138 tahun dan berdasarkan umur desainnya yaitu 15 tahun maka terdapat 12 test point atau 37,5% test point yang diprediksi tidak dapat mencapai umur desain struktur conveyor.